Upaya Meningkatkan Kefasihan dan Kelancaran Membaca Al-qur’an Melalui Metode Iqro’ pada Santri Asrama Miftahul Huda Sukaraja - Suhartono Suhartono; Ahmad Sodikin; Ahmad Ulin Ni’am (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2020)
Efforts to improve fluency and fluency in reading the Qur'an through the Iqro method for Miftahul Huda Sukaraja Dormitory students are carried out with the aim of increasing fluency and fluency in reading the Qur'an in Miftahul Huda Sukaraja Dormitory students. The approach used in the implementation of community service is a functional approach. The method used in the implementation of activities is the Iqro 'learning method. one method of how to quickly learn to read the Qur'an. The results obtained from this activity were that the Miftahul Huda Sukaraja dormitory students experienced an increase in their ability to read the Qur'an in terms of fluency and fluency in accordance with the rules of recitation. Of the 10 students who took part in this activity, there were 8 students who were fluent and fluent in reading the Qur'an in accordance with the rules of recitation of 80%, while there were 2 students who were not fluent and fluent in reading the Qur'an 20%.